Contextualizing the Hadith Prohibiting Begging in the Digital Begging Phenomenon on TikTok - Moh. Solikhul Huda; Zulham Qudsi Farizal Alam (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
The practice of digital begging on TikTok reflects a shift in the perspectives of some Muslims regarding ethical boundaries in the digital public sphere. Activities once considered demeaning are now being exploited as entertainment content to attract attention and profit. This study aims to reevaluate the meaning of the Prophet's hadiths prohibiting begging by adapting them to the context of modern social media. The approach used is qualitative-descriptive, using content analysis of the hadiths and observations of the live streaming phenomenon on TikTok, combined with Islamic ethical principles and the maqāṣid shari'ah (objectives of Islamic law). The results indicate that this practice contradicts core Islamic values, particularly those concerning maintaining self-respect and obtaining sustenance through honorable means. The hadiths studied are not only legally prohibitive but also contain moral values that lead to independence and self-respect. The main finding of this study is that a contextual approach can open new understandings that are more relevant to the challenges of the times, so that the hadiths remain present as ethical guidelines in building a distinguished digital culture.